2009
DOI: 10.1177/0961203309104392
|View full text |Cite
|
Sign up to set email alerts
|

Time to neuropsychiatric damage occurrence in LUMINA (LXVI): a multi-ethnic lupus cohort

Abstract: The aims of this study were to examine the predictors of time-to-neuropsychiatric (NP) damage and its impact on mortality in 632 systemic lupus erythematosus (SLE) African American, Hispanic and Caucasian LUMINA patients, age ≥ 16 years and disease duration ≤ 5 years at baseline (T0). Time-to-NP damage and its impact on mortality were examined by Cox proportional hazards regressions. One-hundred eighty-five (29.3%) patients developed NP-damage over a mean (SD) disease duration of 5.6 (3.7) years. After adjusti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 39 publications
0
18
0
2
Order By: Relevance
“…Although a greater incidence of neurological involvement in females and an increased risk of seizures in males have been reported, there is limited evidence to support an association between gender and NPSLE since most of the studies do not provide correction for important confounders such as comorbidities [ 5 7 ]. NP manifestations are more frequently seen in African descendants, Hispanics, and Asians than in White individuals;[ 8 – 10 ] however, NP damage occurs more frequently among White patients, as described in the LUMINA and Maryland cohorts [ 11 , 12 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…Although a greater incidence of neurological involvement in females and an increased risk of seizures in males have been reported, there is limited evidence to support an association between gender and NPSLE since most of the studies do not provide correction for important confounders such as comorbidities [ 5 7 ]. NP manifestations are more frequently seen in African descendants, Hispanics, and Asians than in White individuals;[ 8 – 10 ] however, NP damage occurs more frequently among White patients, as described in the LUMINA and Maryland cohorts [ 11 , 12 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…Although it is difficult to make generalizations about the risk profile for seizures and damage from seizures, the results of these two studies suggest that lupus-related seizures are likely to be seen in younger lupus patients with more severe disease. In addition, the LUMINA group noted that older age, Caucasian ethnicity, disease activity, and abnormal illness-related behaviors were associated with a shorter time to the development of neuropsychiatric damage, while the use of hydroxychloroquine and the use of only medium-dose prednisone were associated with a longer time (eg, prevention of) to development of neuropsychiatric damage [17]. Neuropsychiatric "organ damage" mat be prevented by, for instance, treatment of antiphospholipid antibodies via anticoagulation.…”
Section: Neuropsychiatric Damage Resulting From Lupusmentioning
confidence: 98%
“…Very few studies have been conducted assessing the role of drugs in the prevention of NPSLE events. In the LUMINA cohort, 60 hydroxychloroquine and moderate prednisolone dose delayed the first NPSLE manifestation, regardless of the type of event. The SALUD study 61 showed that aspirin improved cognitive function in older patients with risk factors.…”
Section: Managementmentioning
confidence: 89%